Analisis Semiotika Novel Hujan Karya Tere Liye dan Relevansinya Terhadap Bahan Ajar Novel Di SMA - Yanti, Meli Rindi; Nurhasanah, Een; Hartati, Dian (Peneliti.net, 2024)
The purpose of this study is to describe the meaning of the novella as well as compiling teaching materials as a utilization of research results. The research approach applies a qualitative approach. The research method applies an analytic descriptive method. The disassembly of meaning applies Ferdinand De Saussure's semiotic theory in the form of signifiers and signifieds. Novel research subjects Rain Karya Tere Liye.While the object of this research is meaning. Data collection techniques used are observation techniques, library techniques, reading techniques, and note-taking techniques. Data analysis techniques in research are data reduction, data presentation, and conclusion. The results of the study show markers in the form of overpopulation, natural disasters, damaged climates, and human extinction as signs of an unpleasant place that has a dystopia meaning. The preparation handout based on KD 3.9 analyzes the content and language of the novel on high school-level novel material.